HLA Does Not Impact on Short-Medium-Term Antibody Response to Preventive Anti-SARS-Cov-2 Vaccine - Ragone, Concetta; Meola, Serena; Fiorillo, Pasqualina C.; Penta, Roberta; Auriemma, Laura; Tornesello, Maria Lina; Miscio, Leonardo; Cavalcanti, Ernesta; Botti, Gerardo; Buonaguro, Franco M.; Bianchi, Attilio; Buonaguro, Luigi; et al. (Frontiers in Immunology, 2021)
The response to anti-SARS-Cov-2 preventive vaccine shows high inter-personal variability at short and medium term. One of the explanations might be the individual HLA allelic variants. Indeed, B cell response is stimulated and sustained by CD4+ T helper cells activated by antigens presented by HLA-class II alleles on antigen presenting cells (APCs). The impact of the number of antigens binding to HLA class-II alleles on the antibody response to the COVID vaccine has been assessed in a cohort of 56 healthcare workers who received the full schedule of the Pfizer-BioNTech BNT162b2 vaccine. Such vaccine is based on the entire spike protein of the SARS-CoV-2. Ab titers have been evaluated 2 weeks after the first dose as well as 2 weeks and 4 months after the boosting dose. HLA-DRB1 and DBQ1 for each of the vaccinees has been assessed and strong binders have been predicted. The analysis showed no significant correlation between the short-medium term Ab titers and the number of strong binders (SB) for each individual. These results indicate that levels of Ab response to the RBD is not dependent on HLA class II allele, ensuring an equivalent efficacy at global level of the currently used vaccines. Furthermore, the pattern of persistence in Ab titer does not correlate with specific alleles nor with the number of SBs.